Multiple cutaneous telangiectasias after the use of trastuzumab: a case report - Bevilaqua, Mariele; de Jesus, Luyze Homem; Ferreira, Iago Gonçalves; Botene Ribolli, Gustavo; Eugenio Santiago Escovar, Carlos (Clinical and Biomedical Research, 2023)
We aim to report a particular case of cutaneous telangiectasias on the arms after immunotherapy with trastuzumab plus paclitaxel to treat breast cancer. New oncology therapies reflect a major advance in cancer treatment. They greatly increase survival; however, they still cause certain adverse cutaneous events that should be taken into account for their proper management.